Theoretical and methodological aspects of personal brand formation in the digital environment - G. V. Dovzhik; V. N. Dovzhik; S. A. Musatova (Цифровая социология)
The article considers the theoretical and methodological aspects of the formation of a personal brand, describes modern approaches to the interpretation of the concepts of brand and personality brand. The main structural elements of a personal brand are analysed, its socio-psychological essence is determined. The emphasis is made on the practical significance of the formation of a personal brand, the components, properties and areas of application of a personal brand are considered.The models of personality brand formation in both offline and online environment are described in accordance with the structural and substantive transformations currently taking place in the information sphere and the factors that influence the effectiveness of communication through a personal brand. These are, first of all, such factors as the widespread of artificial intelligence technologies into everyday life, tools for logical data integration, a significant increase in the number of Internet users. All of the above factors largely determine the nature and degree of social influence of influencers on the behavior of individuals in society.In addition, much attention is paid to the analysis of existing models of personal brand formation, which form the theoretical and methodological basis of a personal brand. If we consider a brand as a tool that stimulates the consumer to a certain action, then in the case of a product brand, such an action will be the fact of buying a product or service directly. If we are talking about a personal brand, then the frequency of consumption of content created by a particular media personality will act as an action. In turn, it is possible to increase the frequency of content consumption by choosing the optimal model of brand communication with consumers. That is why it is especially relevant to study the theoretical and methodological aspects of the formation of a personal brand through online tools in the process of creating a personal brand.